The management of catastrophe insurance risk through the anticipation of the price of CAT bond - Balcerowicz-Szkutnik, Maria; Szkutnik, Włodzimierz (Antycypacja ceny obligacji CAT w zarządzaniu katastrofalnym ryzykiem ubezpieczeniowym, 2011)
he application of financial instruments from the capital market aims at the management of securitization process of the catastrophe risk. This is important with respect to the results of losses caused by catastrophe incidents. The article develops the structure of CAT bonds and their pricing with the use of model of stochastic process of interest rate. The CAT bonds are designed to finance the results of catastrophe incidents. They are similar to the contingent claim capital but in reality they are the financial market instruments. The elaborated approach is illustrated by the distribution of the bond price in the configuration of trigger level for CAT bond forgiveness and its volatility. The direction of possible research is determined by the consideration of moral hazard and basis (market) risk in the pricing process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 158-180
Keywords: ryzyko w ubezpieczeniach; instrumenty finansowe; obligacje; insurance risk; financial instruments; bonds